Comparative eco-physiological potential of a submerged and a free floating aquatic plant to treat domestic wastewater - Patel, D K; Kanungo, V K (Journal of Ecobiotechnology, 2013)
Domestic wastewater treatment has become a remarkable aquatic environmental problem for all over the world. Due to non-availability of cheaper methods and higher cost of treatment plants, municipalities are diverting untreated domestic wastewater in to aquatic bodies like ponds and lakes, where it is causing eutrophication due to higher concentration of nutrients and leads water unhygienic to use. Present research experimented by culturing Hydrilla verticillata, and Pistia stratiotes seprately in domestic wastewater for subsequent seven days over the year. The quality of domestic wastewater before and after the treatment/culture was evaluated by analyzing physico-chemical parameters of domestic wastewater followed by APHA-AWWA-WPCF (1980).The results of physico-chemical analysis of domestic wastewater and estimation of net primary productivity of experimental aquatic plants after the culture have indicated an improvement in water quality and increase in biomass. Both the aquatic plants proved to be efficient in treatment of domestic wastewater and their increased weight in culture has potential value in biomass generation.It is concluded that both the aquatic plants perform significant potential to remove nutrients from domestic wastewater and also showed seasonal variation for the purpose.